Ovos produzidos em diferentes sistemas de alojamento: qualidade e segurança microbiológica, parâmetros físicos, validação e utilização de método multiresíduo para detecção de antimicrobianos e pesticidas - Galvão, Júlia Arantes [UNESP] (2013)
The livestock production has been modified gradually due to several socio-cultural changes worldwide. Increasing the demand for food produced considering animal welfare. In this context also is laying hen raising. New systems are being proposed to improve the living conditions of laying hens, foremost among them the free range (FR). There are few studies which evaluated the quality and safety of eggs produced in these new environments. Thus was proposed in this study the evaluation of eggs and production environment from three laying hens farms (two under the conventional system of creation and one system in FR), two of them (FR and Conventional 1) located on the same property, which decreased the chances of introducing macroclimate and breeder lines bias. Salmonella was surveyed in the production environment, drinking water and food, and the shells of the eggs, which were also enumerated enterobacteria. It was also evaluated the physical quality of the eggs and proceeded to the validation of a multiresidue method for analysis of pesticides and antibiotics, used for quantifying the content of the eggs of the three farms. In FR the largest system Enterobacteriaceae counts (p <0.001) was detected and Salmonella were found in three eggshells and at one feeder (S. Senftenberg), the pathogen was not detected in other environmental samples, or food and water. The eggs of the FR system had lower weight, greater shell thickness and concentration of albumen. The multiresidue method is effective in the recovery of all compounds, enabling the validation of the proposed technique. Enrofloxacin residues were detected in five out of thirty samples from the RF system, they all have extrapolated the MRL of 10μgL-1 established by the Ministry of Agriculture, Livestock and Supply. The FR system showed greater vulnerability and sanitary conditions regarding the presence of antimicrobial residues. As regards physical characteristics, they do not confer to ...